Cineclubismo e territórios digitais: pesquisa sobre cineclubes do Espírito Santo no contexto da pandemia de COVID-19 - Schuina, Lucas Guimarães Blunck (2023)
This research focuses on the ways in which film clubs in the state of Espírito Santo act on digital platforms during the Covid-19 pandemic, which made traditional film club practices impossible but which, on the other hand, favored the emergence of new ways of “watching together, but at a distance”. The objective of the investigation is to make a historical record of this period and to study the impacts on the forms of socialization and aesthetic fruition of audiovisual works by the participants, as well as on the territorialization modes of the film clubs. The study is based on authors who reflect on contemporary film club practices, on new digital platforms and new forms of networked audiovisual and on the concepts of territory and territorialities. Chapter 1 discusses the concepts of territory and territoriality applied to film clubs, and presents the history of film clubs in Brazil and Espírito Santo. Chapter 2 deals with contemporary network audiovisual culture and its impacts on film club activities. Chapter 3 presents the work of data collection and analysis on capixaba film clubs. Through documentary research, 117 film clubs were found in Espírito Santo between 2003 and 2022, of which 29 carried out actions over the internet during the pandemic. Through an online questionnaire, the opinions of people who participated in the activities of the capixaba film clubs during this period were also collected. And through in-depth interviews with representatives of five film clubs in the cities of Águia Branca, Baixo Guandu, Muniz Freire, Vitória and Vila Velha, qualitative information about the film clubs was obtained. From the methodological point of view, this was a participant research, since the author worked at Cineclube Jece Valadão, in Cachoeiro de Itapemirim, during the course of the investigation. The conclusion of the study is that digital media contributed to the film clubs building new partnership networks during the pandemic, but that their participants suffered losses in terms of social interaction and in the relationship with the territories where they are located.